Human Capital Dynamics of Regional Growth in Nigeria: Dynamic Panel Data Approach (Sains Humanika, 2014)
This paper investigates the human capital factors that contribute to the growth of the Nigerian regional growth rates. In particular, it is to determine whether the leading role of human capital factors in other economies could explain the regional growth processes dynamics in Nigeria. If these factors are not applicable, other possible explanations are to be identified for the country’s regional economic growth dynamics profile. Nigerian regional cross sectional data of financial, physical and human capital accumulation were utilized to run a growth accounting regression captured by an aggregate production function. The study uses panel data (cross sectional and time series data) from 1998 to 2008 and employed three (3) panel data models to estimate the dynamics and contribution of human capital factors. The results showed that the initial human capital stock has an influence on the GDP per capita growth rate. Similarly, the Southern regions that had a head start in school attendance have higher thresholds or secondary schools are significant; higher levels of schooling (secondary school) have significant impact on the GDP per capita growth rate. On the other hand, the Northern regions have lower technical frontier; as only the primary school have significant impact on the GDP per capita growth. However the federal financial allocation from the federation accounts was found to be significant across all regions with the exception of the South-South regions, and positive investment in physical assets of education. Thus it implies that regional differences should be taken into account when planning developmental processes.
Keywords: Regional growth; human capital; dynamics; panel data